The effect of partial conversion and fiber delay lines in an OBS switch with a large number of wavelengths (2010)
In this paper, we analyze an optical burst switching (OBS) switch endowed with both wavelength converters (WCs) and fiber delay lines (FDLs) to resolve contention. We consider the case where the number of wavelengths is large by introducing a mean field model that provides exact results when the number of wavelengths tends to infinity. We have confirmed through simulations that the mean field model provides accurate approximations for switches with a large but finite number of wavelengths, which are of interest in view of wavelength division multiplexing (WDM). Furthermore, our model allows a very general behavior for the arrival process and the packet size distribution, as well as two different wavelength allocation policies: minimum horizon and minimum gap. Our results include a detailed analysis of the effect that these parameters have on the burst loss rate, and on the minimum number of WCs required to attain a zero loss rate as the number of wavelengths becomes large. We have found that at high loads there is little value in adding FDLs and, if included, shorter granularities result in fewer WCs required to achieve a zero loss rate. The inclusion of FDLs becomes more significant under mid loads and bursty traffic, where the addition of several FDLs may reduce the conversion requirements. Also, increasing the number of WCs under the minimum horizon policy may worsen the loss rate, while this is never the case for the minimum gap policy.